Evaluation of Oral and Maxillofacial Masses in Sample Received in Pathology Department SMC/SGTH KPK: Evaluation of Oral and Maxillofacial Masses - Hadi , Shamsul; Yaseen, Sana; Yaqoob, Zarka; Ahmad, Shafiq; Tasneem , Maria; Waseem, Fatima (Pakistan Journal of Health Sciences, 2023)
Cysts, polyps and inflammatory process are the major benign tumors of the oral cavity. The SCC, lymphomas, sarcomas of bones and soft tissues and rarely melanomas are malignancies of oral cavity. Distal metastases from of breast carcinoma, lungs, abdominal organs and prostate can occur in oral cavity. The age of these lesions is among less than one year kids up to 85 years old, almost 90% of the patient’s average age of 40 years. These tumors distributed in all over the world especially in the socio-demographic area. Objectives: To evaluate the histopathological outlines of OMF specimens received in pathological Department of SMC/SGTH KPK. Methods: A cross sectional retrospective study. Results: Of a total of 321 samples 164 (51%) were male while 157 (49%) were women with a proportion of M: F=1.05: 1. Mesenchymal tumors, other than osseous tumor, have the maximum quantity of 33.9% cases trailed by epithelioid lesions, 20%, odontogenic masses 5.3%, lesions of salivary gland were 14.6%, lesions of benign cyst were 12.5%, inflammatory lesions 11% and the minimum numbers of oral and maxillofacial specimens was bone tumor with 2.9% cases. From the benign tumors fibro epithelial tumor 23% is the commonest. The SCC was 57%, the largest contributor among all malignancies. Conclusion: Our study demonstrates the variations of age, sex and location in the oral and maxillofacial masses. The malignant masses are common an elderly aged patient, while the benign are more common an early and middle age people.